The Genetic Spectrum of Familial Hypercholesterolemia (FH) in the Iranian Population - R. H. Fairoozy (Nature Portfolio, 2017)
Abstract Familial hypercholesterolemia (FH) is an autosomal dominant disorder associated with premature cardiovascular disease (CVD). Mutations in the LDLR, APOB, and PCSK9 genes are known to cause FH. In this study, we analysed the genetic spectrum of the disease in subjects from the Iranian population with a clinical diagnosis of FH. Samples were collected from 16 children and family members from five different cities of Iran. Probands were screened for mutations in the LDLR, APOB, and PCSK9 genes using next generation sequencing, with results confirmed by Sanger sequencing. The likely pathology of identified variants was examined using in silico tools. Of the probands, 14 had a clinical diagnosis of homozygous FH and two of heterozygous FH. No mutations were found in either APOB or PCSK9, but nine probands were homozygous for seven different LDLR mutations, with p.(Trp577Arg) occurring in three and p.Val806Glyfs*11 occurring in two patients. Two mutations were novel: p.(Leu479Gln) and p.(Glu668*). Seven probands with a clinical diagnosis of FH were mutation negative. This pilot study, integrating clinical and molecular-based techniques, begins to elucidate the FH heterogeneity and the mutation spectrum in the Iranian population. Such information is important for future disease management and cost savings.